2021
DOI: 10.1002/chem.202102492
|View full text |Cite
|
Sign up to set email alerts
|

n‐Butane, iso‐Butane and 1‐Butene Adsorption on Imidazolium‐Based Ionic Liquids Studied with Molecular Beam Techniques

Abstract: The interaction of molecules, especially hydrocarbons, at the gas/ionic liquid (IL) surface plays a crucial role in supported IL catalysis. The dynamics of this process is investigated by measuring the trapping probabilities of nbutane, iso-butane and 1-butene on a set of frozen 1-alkyl-3methylimidazolium-based ILs [C n C 1 Im]X, where n = 4, 8 and X À =Cl À , Br À , [PF 6 ] À and [Tf 2 N] À . The decrease of the initial trapping probability with increasing surface temperature is used to determine the desorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
1
0
0
Order By: Relevance
“…This behavior is interpreted as the blocking of 1-butene adsorption sites by the IL, until at θ IL = 0.55 ML the Pt(111) surface is completely covered by ILs. This finding is in line with previous studies from our group, which showed that (1) 1-butene adsorption is not expected at 180 K on pure IL surfaces 56 and (2) ∼0.5 ML of IL is needed to wet a metal surface completely. 31 For 1,3-butadiene, a similar linear decrease of θ butadiene,SAT is observed for increasing θ IL (see Figure 3b, full squares).…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…This behavior is interpreted as the blocking of 1-butene adsorption sites by the IL, until at θ IL = 0.55 ML the Pt(111) surface is completely covered by ILs. This finding is in line with previous studies from our group, which showed that (1) 1-butene adsorption is not expected at 180 K on pure IL surfaces 56 and (2) ∼0.5 ML of IL is needed to wet a metal surface completely. 31 For 1,3-butadiene, a similar linear decrease of θ butadiene,SAT is observed for increasing θ IL (see Figure 3b, full squares).…”
Section: ■ Results and Discussionsupporting
confidence: 93%